Beyond Grammar-Translation: CLIL as a Communicative Strategy for Arabic Speaking Development at Madrasah Tsanawiyah Level - Nazwa Qomariyah; Ro'fat Hizmatul Himmah, Ro'fat Hizmatul Himmah; Ro'fat Hizmatul Himmah (Postgraduate of IAIN Metro Lampung Indonesia, 2026)
The development of Arabic speaking skills in madrasahs is often hindered by a theoretical teaching pattern with minimal communicative practice. This study aims to analyze the effectiveness of the Content and Language Integrated Learning (CLIL) approach on the speaking skills of eighth-grade students at MTsN 9 Banyuwangi. Using a quasi-experimental quantitative method thru a pretest-posttest control group design, this study involved 50 students as the sample. Data were collected via oral tests using an analytic rubric, then analyzed with an independent t-test and N-Gain test. The research results showed a significant difference in posttest scores (p < 0.001), where the experimental group achieved a high category increase (N-Gain 0.7105), surpassing the control group which was in the moderate category (0.3703). The novelty of this research lies in the modification of content-based oral production tasks through the 4C framework to stimulate contextual fluency. This research suggests the implementation of CLIL as an innovative strategy in Arabic language learning at madrasahs, noting the need for further studies on its long-term impact.